INTERNATIONAL LEGAL COOPERATION OF THE PROSECUTORS BODIES AGAINST CORRUPTION (TSUL LEGAL REPORT, 2026)
The article focuses on the issues of international cooperation of the Prosecutors’ Office on provision of legal assistance in criminal matters, such as corruption. Besides that, the article is dedicated to the matters concerning the cooperation Prosecutors’ Office in terms of fighting against crime within the regional scope of international organizations. The author of this scientific article revealed the essence and main directions of international cooperation of the Prosecutors’ Office of the Republic of Uzbekistan to combat transnational crime and corruption in the context of digital globalization and the integration of the world community.Moreover, the relevance of the research topic is because the commission of such crimes is characterized by the use of modern technical means and high-tech facilities of air and land transport, a high transcontinental level of organization and real support of many, including illegal, financial sources. The predicted result of such activities was a significant increase in the number of serious crimes of a transnational nature.